Acute, subacute toxicity and genotoxic effect of a hydroethanolic extract of the cashew (Anacardium occidentale L.) - Konan, Nzi Andre; Bacchi, Elfriede Marianne; Lincopan, Nilton; Varela, Soraya Duarte; Varanda, Eliana Aparecida [UNESP] (Elsevier B.V., 2007)
Anacardium occidentale L. (Anacardiaceae), popularly known as cajueiro is a native plant to Brazil, and largely used in popular medicine to treat ulcers, hypertension and diarrhea. In the present study, acute, 30-day subacute toxicity and genotoxicity assays were carried out. The crude extract did not produce toxic symptoms in rats in doses up to 2000 mg/kg. Based on biochemical analyses of renal and hepato-biliary functions, such as the level of urea, creatinine, transaminases and alkaline phosphatase, we determined that the extract is generally tolerated by rats. This was also confirmed by hematological and histopathological exams. Genotoxicity was accessed by the Ames test in Salmonella typhimurium strains TA97, TA98, TA 100, TA 102 and by the bone marrow micronucleus test in mice. The extract was shown to induce frameshift, base pair substitution and damage to the chromosomes. However, this effect was less deleterious than the clastogenic effect of ciclophosphamide. (c) 2006 Elsevier B.V.. All rights reserved.
Keywords: Anacardium occidentale; acute toxicity; subacute toxicity; genotoxicity